Persistent ENT Manifestations in Individuals who Recovered from COVID-19: A Systematic Review - Sharma, Akriti; Jakhar, Rohit Kumar; Kakkar, Vikas; Singal, Garima (International Archives of Otorhinolaryngology, 2024)
Introduction Long coronavirus disease (COVID) refers to the persistence of symptoms long after the recovery from the acute phase of the illness, and it is due to the interplay of various inflammatory mechanisms. This has led to emergence of new deficits, including otorhinolaryngological symptoms, in patients wo have recovered from COVID. The plethora of otorhinolaryngological symptoms associated with long COVID are tinnitus, sensorineural hearing loss (SNHL), vertigo, nasal congestion, sinonasal discomfort, hyposmia/anosmia, dysgeusia, sore throat, dry cough, dyspnea, dysphagia, and hoarseness of voice.Objective To evaluate the possible ENT symptoms in patients wo have recovered from COVID and to combine those findings with our experience.Data Synthesis We conducted a search on the PubMed, ENT Cochrane, Web of Science, and Google Scholar databases, and a total of 44 studies were selected for the present review.Conclusion Otorhinolaryngological complications such as tinnitus, SNHL, vertigo, nasal congestion, sinonasal discomfort, hyposmia/anosmia, dysgeusia, sore throat, dry cough, dyspnea, dysphagia, and hoarseness of voice have been widely reported among in long-COVID patients.
Keywords: long COVID; SARS-CoV-2; otorhinolaryngological manifestations